Distribución geográfica potencial de Bursera graveolens Kunth. en el norte del Perú, 2023 - Melendez Torres, Martha Isabel (2025)
Using the MaxEnt software, the potential geographic distribution of Bursera graveolens Kunth was modeled in northern Peru, covering the regions of Tumbes, Piura, Lambayeque, and Cajamarca. The results indicated that the district of Suyo, located in the province of Ayabaca, represents one of the areas with the highest ecological suitability for this species; therefore, it was selected to assess the conservation status of its vegetation. For this purpose, Sentinel-2 satellite imagery and the Normalized Difference Vegetation Index (NDVI) were analyzed for the period 2019–2023. Through the application of the Mann-Kendall trend test and linear regression analysis, decreasing trends in NDVI values were observed in Suyo. However, these variations are likely associated with the climatic seasonality typical of tropical dry forest ecosystems, rather than reflecting structural degradation of the habitat. These findings not only establish a critical baseline for the monitoring of Bursera graveolens Kunth, but also provide a comprehensive methodological framework for future conservation studies in the dry forests of northern Peru, where environmental changes and anthropogenic pressures pose significant threats to biodiversity.